2024
DOI: 10.1007/s11192-024-04972-x
|View full text |Cite
|
Sign up to set email alerts
|

Authorship conflicts in academia: an international cross-discipline survey

Elizaveta Savchenko,
Ariel Rosenfeld

Abstract: Collaboration among scholars has emerged as a significant characteristic of contemporary science. As a result, the number of authors listed in publications continues to rise steadily. Unfortunately, determining the authors to be included in the byline and their respective order entails multiple difficulties which often lead to conflicts. Despite the large volume of literature about conflicts in academia, it remains unclear how exactly these are distributed over the main socio-demographic properties, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…The issue of merit and recognition of author contributions within research teams is a contentious one, and can lead to conflicts within the academic community (Savchenko & Rosenfeld, 2024;Smith et al, 2020). In their survey of more than 8,000 researchers, Smith et al (2020) showed that nearly half of respondents had encountered reported disagreements regarding authorship naming at least once in their career.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of merit and recognition of author contributions within research teams is a contentious one, and can lead to conflicts within the academic community (Savchenko & Rosenfeld, 2024;Smith et al, 2020). In their survey of more than 8,000 researchers, Smith et al (2020) showed that nearly half of respondents had encountered reported disagreements regarding authorship naming at least once in their career.…”
Section: Introductionmentioning
confidence: 99%
“…In their survey of more than 8,000 researchers, Smith et al (2020) showed that nearly half of respondents had encountered reported disagreements regarding authorship naming at least once in their career. Furthermore, a recent international and interdisciplinary survey conducted by Savchenko and Rosenfeld (2024) with 752 scholars from 41 research fields and 93 countries revealed that conflicts regarding authorship credit allocation often arise early in academic careers. Specifically, nearly one in four participants reported experiencing at least one conflict with an advisor during their master's or doctoral studies.…”
Section: Introductionmentioning
confidence: 99%